EIS/VIMP screening of archaeological bronze corrosion products - Redondo-Marugán, Jorge (2019)
Electrochemical impedance measurements were applied to microparticulate deposits of copper corrosion products attached to graphite electrodes in contact with different aqueous electrolytes (0.25 M HAc/NaAc (pH 4.75), 0.10 M HCl and 0.10 M HClO4) and the application of an interval of potentials between +0.25V to -0.75V. The conditions of operation were selected from a compromise between repeatability and sensitivity, being 0.10 M HClO4 and bias potential of 0.25 V adopted. The electrochemical impedance data were modeled on the basis of available equivalent circuits for corroded metal surfaces and the correlation between several pairs of circuit elements provided the characterization of different corrosion compounds regardless the amount of microparticulate solid on the electrode. Electrochemical grouping of samples from the archaeological Roman site of Gadara (Jordan, 4th century AD) suggests different provenances/manufacturing techniques, consistent with voltammetry of immobilized particles (VIMP) measurements. Thus, illustrating the capabilities of the intersection of such techniques in the archaeometric domain.